First real-time imaging of bronchoscopic lung volume reduction by electrical impedance tomography - Torsani, Vinicius; Cardoso, Paulo Francisco Guerreiro; Borges, João Batista; Gomes, Susimeire; Moriya, Henrique Takachi; Cruz, Andrea Fonseca da; Santiago, Roberta Ribeiro de Santis; Nagao, Cristopher Kengo; Fitipaldi, Mariana Fernandes; Beraldo, Marcelo do Amaral; Junior, Marcus Henrique Victor; Mlček, Mikuláš; et al. (Respiratory research, 2024)
BACKGROUND: Bronchoscopic lung volume reduction (BLVR) with one-way endobronchial valves (EBV) has better outcomes when the target lobe has poor collateral ventilation, resulting in complete lobe atelectasis. High-inspired oxygen fraction (FIO2) promotes atelectasis through faster gas absorption after airway occlusion, but its application during BLVR with EBV has been poorly understood. We aimed to investigate the real-time effects of FIO2 on regional lung volumes and regional ventilation/perfusion by electrical impedance tomography (EIT) during BLVR with EBV. METHODS: Six piglets were submitted to left lower lobe occlusion by a balloon-catheter and EBV valves with FIO2 0.5 and 1.0. Regional end-expiratory lung impedances (EELI) and regional ventilation/perfusion were monitored. Local pocket pressure measurements were obtained (balloon occlusion method). One animal underwent simultaneous acquisitions of computed tomography (CT) and EIT. Regions-of-interest (ROIs) were right and left hemithoraces. RESULTS: Following balloon occlusion, a steep decrease in left ROI-EELI with FIO2 1.0 occurred, 3-fold greater than with 0.5 (p < 0.001). Higher FIO2 also enhanced the final volume reduction (ROI-EELI) achieved by each valve (p < 0.01). CT analysis confirmed the denser atelectasis and greater volume reduction achieved by higher FIO2 (1.0) during balloon occlusion or during valve placement. CT and pocket pressure data agreed well with EIT findings, indicating greater strain redistribution with higher FIO2. CONCLUSIONS: EIT demonstrated in real-time a faster and more complete volume reduction in the occluded lung regions under high FIO2 (1.0), as compared to 0.5. Immediate changes in the ventilation and perfusion of ipsilateral non-target lung regions were also detected, providing better estimates of the full impact of each valve in place. TRIAL REGISTRATION: Not applicable.
Keywords: bronchoskopie; Pneumonectomy; Lung Volume Measurements; Absorption atelectasis; měření objemu plic; Lung; zvířata; plíce; časové faktory; Swine; pneumektomie; Endobronchial valves; Lung volume reduction; Tomography; Electrical impedance tomography; Emphysema; Animals; elektrická impedance; Pulmonary Atelectasis; tomografie; Electric Impedance; Time Factors; prasata; Bronchoscopy; atelektáza